Clean and healthy environmental behavior in terms of malnutrition and sanitation - . Nuraeni; N.I. Hawa; D. Utari; E. Parahyanti (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: A lousy environment has the potential to be a predictor of disease transmission, which ultimately results in malnutrition among children. Meanwhile, the mother's role is crucial in the first 1000 days of life. This research aimed to determine the determinants of maternal behavior in preventing chronic malnutrition in children on the basis of environmental aspects.METHODS: This cross-sectional study with a quantitative design was conducted in Surabaya, Indonesia, with a sample of 208 pregnant women and 222 mothers of toddlers. A questionnaire was used to identify information related to the dependent variable, chronic malnutritional prevention behavior, on the basis of environmental aspects, and independent variables related to the determinants of maternal behavior. Data were analyzed via Chi-square test using the Statistical Program for Social Sciences.FINDINGS: As many as 80.8 percent of pregnant women and 65.8 percent of mothers under five had good chronic malnutritionchronic malnutrition prevention behavior. The perception of behavioral control in using clean water is significantly related to the behavior of pregnant women and mothers of toddlers, with significance values of 0.012 and 0.013, respectively. The perceived behavioral control towards washing hands with soap has a significant relationship with the behavior of pregnant women and mothers of toddlers, with significance values of 0.003 and 0.005, respectively. Pregnant women with poor behavioral control in washing their hands with clean water and soap were 2.963 times more likely to have poor chronic malnutritionchronic malnutritional prevention behavior than the comparison group. Subjective norms of using clean water and washing hands with clean water and soap in pregnant women are significantly related to chronic malnutritionchronic malnutrition prevention behavior, with significance values of 0.011 and 0.049, respectively, and odds ratios of 2 and 2.280, respectively.CONCLUSION: Environment-based chronic malnutritionchronic malnutritional prevention behavior in mothers is primarily influenced by perceived behavioral control and subjective norms. The family can be part of the subjective norms that drive aspects of attitudes and perceptions of behavioral control related to environment-based chronic malnutritionchronic malnutrition prevention practices. Meanwhile, the aspects of controlling maternal behavior can be intervened through efforts to minimize obstacles and increase the perception of benefits from behavior to prevent chronic malnutrition. Maternal behavioral change interventions could encourage the implementation of good behavior in preventing malnutrition in children. In the end, children could learn the behavior given by their mothers and adopt it.